Gender matters: Private sector training in Vietnamese SMEs - Benedikte Bjerge; Nina Torm; Neda Trifkovic (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
In many developing countries the skill base is a cause of concern with respect to international competition. Firm-provided training is generally seen as an important tool for bridging the skills gap between labour force and private sector demand. Yet little is known about how successful such training may be in closing the gender wage gap. We use a matched employer-employee panel dataset to assess why firms train and whether formal training affects wage outcomes in Vietnamese SMEs. Training is generally found to be firm-sponsored and specific in nature. We find that training is associated with a wage increase of 7-22 per cent for female workers only, depending on the analytical approach taken. We also show evidence that the wage increase is associated only with on-the-job training and that lower ability workers are more likely to be trained. Our findings indicate that, at least in Viet Nam, firm-sponsored on-the-job training helps close the gender wage gap.
Keywords: J31; J16; M53; O53; 330; training; wage; SME; Viet Nam